Bertahan, Terluka: Fenomena Toxic relationship akibat Kegagalan Komunikasi di Kalangan Generasi Z - Asyraf, J. A (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to identify the phenomenon of toxic relationships caused by communication failures in interpersonal relationships among Generation Z. It also seeks to understand why individuals remain in unhealthy relationships despite experiencing emotional harm. A qualitative descriptive method was employed, using a case study approach and in-depth interviews with Gen Z individuals in Bandung City who have experienced toxic relationships. The results indicate that communication failures such as one-sided assumptions, silent treatment, and emotional invalidation are the root causes of damaging relationships. Additionally, emotional dependence, hope for change, and low emotional literacy were identified as common reasons for staying in such relationships. This research is expected to contribute to the development of healthy communication awareness and psychosocial interventions for young generations